Optimizing rheological behavior of glass-based sealant inks for robocasting deposition: A design of experiment approach - A. Baggio; D. Dalmazzo; F. D’Isanto; E. Santagata; D. Basso; D. Gaia; M. Salvo; F. Smeacetto (Materials & Design)
Robocasting is a commonly used method for depositing ceramic and glass inks, especially for glass-based sealants. Developing an ink recipe that optimizes an existing process can be a complex and time-consuming task. This study utilized a statistical approach based on the Design of Experiment theories to fine-tune the rheological properties of a water-based glass-based suspension with a limited number of experiments.The key components of the sealant were characterized with a scanning electron microscope, and a fractional factorial design 2(5-1) was implemented to investigate the influence of each component on the rheological characteristics of the ink within a predefined domain of variation. The information obtained and the resulting models were useful in designing a new formulation that closely mimics the rheology of a state-of-the-art ink formulation.This analytical approach not only facilitated the development of a new sealant ink but also enabled its seamless integration into an existing industrial robocasting deposition process without requiring additional adjustments. The study contributes to a better understanding of the influence of each ink component on the rheological behavior and to the design of a new formulation with rheological characteristics very close to those of a reference paste.